Characterization of cytokine binding and its implications in the physiology of Aggregatibacter actinomycetemcomitans - Ahlstrand, Tuuli (fi=Turun yliopisto|en=University of Turku|, 2019)
Bacterial pathogens cause severe infections in humans. The emergence of multiresistant bacteria requires the development of new antimicrobial strategies. Bacteria utilize various virulence mechanisms to promote their survival in the host organism. Among these virulence mechanisms, we may find novel targets for antimicrobial treatment. This thesis concerns a virulence mechanism of an oral bacterium that may disturb the human immune response and potentially increase bacterial virulence. The model organism for this study is Aggregatibacter actinomycetemcomitans, a gram-negative opportunistic pathogen that forms biofilms on the surface of teeth and causes an inflammatory oral disease called periodontitis. Bacteria living in biofilms are more resistant to antimicrobial compounds and the mechanisms associated with their virulence are poorly known. Previously, it was discovered that A. actinomycetemcomitans binds and uptakes human inflammatory cytokines, which may modulate the local inflammatory milieu and weaken the host defense. This thesis consists of four parts, each published as a separate article in scientific journals. In the beginning of this thesis I discovered a novel cytokine-binding outer membrane protein, BilRI, in A. actinomycetemcomitans. BilRI was located on the outer membrane of A. actinomycetemcomitans and interacted with the human cytokine IL-1β. The second article showed that BilRI binds multiple cytokines and has an intrinsically disordered structure. In the third article, I showed that a major bacterial cell wall component, lipopolysaccharide, interacted with certain cytokines. This interaction was shown in many A. actinomycetemcomitans serotypes using intact bacterial cells, outer membrane vesicles and isolated lipopolysaccharides. Further, some information was obtained about the location of the interaction site. In the fourth article, I found that a channel protein of A. actinomycetemcomitans, HofQ, binds human cytokines, such as IL-1β and IL-8. This protein has been previously associated with DNA uptake, providing a possible link between the naturally occurring uptake of extracellular DNA and the cytokine uptake mechanism in bacteria. This thesis showed the cytokine binding of A. actinomycetemcomitans outer membrane molecules and how they affected the physiology of the pathogen. Further research is needed regarding the roles of these molecules in the virulence of A. actinomycetemcomitans.

Patogeeniset bakteerit aiheuttavat ihmisille vakavia infektioita. Nykyisille antibiooteille multiresistenttien bakteerien yleistyminen vaatii uusien antimikrobistrategioiden kehittämistä. Bakteerit käyttävät useita virulenssimekanismeja, jotka auttavat niitä selviytymään isäntäorganismissa. Näiden virulenssimekanismien joukosta saattaisi löytyä uusia antimikrobihoidon kohteita. Väitöskirjassa tutkittiin suubakteerin virulenssimekanismia, joka saattaa häiritä ihmisen immuunipuolustusta ja lisätä bakteerin virulenssia. Työssä käytettiin malliorganismina Aggregatibacter actinomycetemcomitans – bakteeria, joka on gram-negatiivinen opportunistinen patogeeni. Se muodostaa biofilmejä hampaiden pinnalle ja aiheuttaa suun tulehdussairautta parodontiittia. Biofilmeissä elävät bakteerit ovat vastustuskykyisempiä antimikrobisille aineille ja niiden virulenssiin liittyviä mekanismeja tunnetaan huonosti. Aiemmin on havaittu, että A. actinomycetemcomitans sitoo ja siirtää sisäänsä ihmisen tulehduksenvälittäjäaineita, sytokiineja. Tämä saattaa muuttaa paikallista tulehdusympäristöä ja heikentää isännän puolustusta. Väitöskirjatutkimukseni koostuu neljästä osatyöstä, jotka on julkaistu erillisinä artikkeleina tieteellisissä lehdissä. Väitöskirjatutkimukseni alussa löysin A. actinomycetemcomitansista uuden sytokiineja sitovan ulkokalvon proteiinin, BilRI:n. BilRI tuottui bakteerin ulkokalvolle ja sitoutui IL-1β:aan. Toisessa osatyössä BilRI:n havaittiin sitovan useita sytokiineja ja olevan rakenteeltaan luonnostaan järjestäytymätön. Kolmannessa osatyössä osoitin, että bakteerin soluseinän komponetti lipopolysakkaridi vuorovaikuttaa joidenkin sytokiinien kanssa. Vuorovaikutus osoitettiin useiden eri A. actinomycetemcomitans serotyyppien kanssa kokonaisilla bakteerisoluilla, ulkokalvon vesikkeleillä sekä eristetyillä lipopolysakkarideillä. Lisäksi vuorovaikutuskohdan sijainnista saatiin tietoa. Neljännessä osatyössä havaitsin, että HofQ-kanavaproteiini sitoo myös ihmisen sytokiineja, kuten IL-1β:aa ja IL-8:aa. Aiemmin tämän kanavaproteiinin on havaittu osallistuvan DNA:n sisäänottoon, joten työ osoittaa mahdollisen yhteyden luonnollisen solunulkoisen DNA:n sisäänoton ja sytokiinien sisäänoton välillä. Väitöskirjassa osoitettiin A. actinomycetemcomitansin ulkokalvon molekyylien sitoutuminen sytokiineihin sekä niiden vaikutuksia bakteerin fysiologiaan. Näiden molekyylien vaikutuksista A. actinomycetemcomitansin virulenssiin tarvitaan vielä lisää tutkimusta.